Impact of chemotherapy upon quality of life for patients with chronic myeloid leukemia - Abdullah, adel; Mansour, Khalidah; Abdullah, adel (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To determine the impact of Chemotherapy upon the quality of life for patients with chronic myeloidleukemia in Baghdad city.Methodology: A descriptive study design was carried out The study was initiated from 30 January 2011 to October2011.A purposive (non–probability) sample consisted of (130) patients with a chronic myeloid leukemia ,Whoattended to Baghdad Teaching Hospital and National Center for Research and Treatment of Hematology. Thesample criteria was the patients who were 18 years old and above, excluding the patients who suffered frompsychological problems and other chronic illnesses .A questionnaire was adopted and developed from EuropeanOrganization Research and treatment of Cancer Quality of life group (EORTC- QoLG).The questionnaire wasdesigned and composed of two parts: the first part deals with the sociodemographic clinical characteristics of CMLpatients, the second part includes six domains of the quality of life which are symptoms (disease and treatmentrelated),psychosocial ,infertility, satisfaction, adherence to therapy ,and body image .The reliability and validity ofquestionnaire were determined through a pilot study by correlation coefficient method, while the content validityof the questionnaire was determined through a panel of experts. The data was collected through the application ofthe questionnaire , the self-report ,interview technique and patient sheets. The data was analyzed through thedescriptive data analysis approach, which included frequency, percentage, standard deviation, mean, mean ofscore and inferential data approach (T test, ANOVA).Results: The present results revealed that the majority (33.84%), of the study sample were within the age groups(31 –40) years. The results showed that the mean score were low QoL with all domains except satisfaction aspectindicated high QoL. There was a statistically significant association between QoL as a general and sex, maritalstatus, occupation, crowding index, duration of disease, phase of disease and performance status, while there wasno statistically significant association between QoL as a general and age, socioeconomic status, and educationallevel. The revealed no effect of disease and treatment related on quality of life.Recommendation: The study recommended the establishment of hematology center, bone marrowtransplantation, the provision of genetic test, according to international standards and the second generation oftreatment